A global dataset of human mobility - Ho Fai Chan; Ahmed Skali; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2020)
In the midst of the COVID-19 pandemic currently affecting every corner of the globe, there is a critical need for understanding and mapping human movement in order to formulate appropriate scientific and policy responses. To this end, we provide ready-to-use indexes of human mobility spanning 131 countries and territories and 818 sub-national regions across a time period between 16 February 2020 to 29 March 2020. We extract these data from Google's newly released mobility reports, which cover phone-tracking-based changes in mobility across several types of locations, including retail and recreation, grocery stores and pharmacies, parks, transit stations, workplaces, and private residences. We make these data immediately available to the scientific community and the broader public at https://osf.io/rzd8k/ in order to support research into the COVID-19 pandemic.
Keywords: 330; Menschen; Mobilität; Indexberechnung; Welt